Development of a Survey to Assess the Acceptability of an Innovative Contraception Practice among Rural Pharmacists - Michael Wong; Judith A. Soon; Peter J. Zed; Wendy V. Norman (MDPI AG, 2014)
Improved access to effective contraceptive methods is needed in Canada, particularly in rural areas, where unintended pregnancy rates are high and specific sexual health services may be further away. A rural pharmacist may be the most accessible health care professional. Pharmacy practice increasingly incorporates cognitive services. In Canada many provinces allow pharmacists to independently prescribe for some indications, but not for hormonal contraception. To assess the acceptability for the implementation of this innovative practice in Canada, we developed and piloted a survey instrument. We chose questions to address the components for adoption and change described in Rogers' "diffusion of innovations" theory. The proposed instrument was iteratively reviewed by 12 experts, then focus group tested among eight pharmacists or students to improve the instrument for face validity, readability, consistency and relevancy to community pharmacists in the Canadian context. We then pilot tested the survey among urban and rural pharmacies. 4% of urban and 35% of rural pharmacies returned pilot surveys. Internal consistency on repeated re-phrased questions was high (Cronbach's Alpha = 0.901). We present our process for the development of a survey instrument to assess the acceptability and feasibility among Canadian community pharmacists for the innovative practice of the independent prescribing of hormonal contraception.